2009
DOI: 10.1088/0004-637x/703/2/2232
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Correlation Weak Lensing of SDSS Galaxy Clusters. Iii. Mass-to-Light Ratios

Abstract: We present measurements of the excess mass-to-light ratio measured around MaxBCG galaxy clusters observed in the SDSS. This red sequence cluster sample includes objects from small groups with M 200 ∼ 5 × 10 12 h −1 M ⊙ to clusters with M 200 ∼ 10 15 h −1 M ⊙ . Using cross-correlation weak lensing, we measure the excess mass density profile above the universal mean ∆ρ(r) = ρ(r) −ρ for clusters in bins of richness and optical luminosity. We also measure the excess luminosity density ∆ℓ(r) = ℓ(r) −l measured in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 63 publications
(107 reference statements)
6
90
1
Order By: Relevance
“…For a cluster with the same number of N 200 (Sect. 4.3) galaxies as J0454, Sheldon et al (2009a) predict M 200 /L0.25 i = 200 ± 30 h. Given the scatter present in the luminosity and the mass of a given N 200 bin (see Sheldon et al 2009b,a), J0454 does not appear exceptionally over-luminous compared to non-fossil systems. The contribution of the BGG to the total luminosity in i-band within r 200 is 38%.…”
Section: Dynamic Disturbances X-ray Offsets and Cooling Flowsmentioning
confidence: 86%
See 1 more Smart Citation
“…For a cluster with the same number of N 200 (Sect. 4.3) galaxies as J0454, Sheldon et al (2009a) predict M 200 /L0.25 i = 200 ± 30 h. Given the scatter present in the luminosity and the mass of a given N 200 bin (see Sheldon et al 2009b,a), J0454 does not appear exceptionally over-luminous compared to non-fossil systems. The contribution of the BGG to the total luminosity in i-band within r 200 is 38%.…”
Section: Dynamic Disturbances X-ray Offsets and Cooling Flowsmentioning
confidence: 86%
“…This also applies to J0454, for which the data are insufficient to derive a temperature map with sufficient resolution to establish the non-existence of a cooling core. Sheldon et al (2009a) have obtained mass-to-light ratios for the maxBCG cluster sample in SDSS, using weak lensing to estimate M 200 . The total luminosity within r 200 was inferred from red sequence galaxies only.…”
Section: Dynamic Disturbances X-ray Offsets and Cooling Flowsmentioning
confidence: 99%
“…From the observations and simulations we have a good understanding of the relation between cluster observables and the total mass of a cluster, for instance Böhringer et al (2012), Sheldon et al (2009), andJohnston et al (2007), which means that the visible components of a cluster represent the underlying dark matter component well. If DM had no preferential scale, this argument should apply in a similar way to superclusters, which means that a supercluster mass probed by the total cluster mass is probably also correlated with the true mass of the supercluster.…”
Section: Mass Fraction Probed By Clustersmentioning
confidence: 99%
“…We integrate these NFW profiles along the LOS and out to a projected radius of 1 Mpc, yielding a total mass of 5.6 × 10 15 M for the 10 clusters. Since Sheldon et al (2009) and Hoekstra et al (2000) have shown that, although cluster centres are dominated by luminous matter, the mass to light ratio (M/L) of clusters within a distance of 1 Mpc is similar to the cluster M/L within larger distances, this ensures that we measure and normalise the SMF in a representative volume. Figure 8 shows the total SMF for the cluster and the field, after normalising by the total masses estimated above.…”
Section: Normalisation Of the Smfmentioning
confidence: 99%